Stenotrophomonas Maltophilia/S. Maltophilia Sepsis Presenting with Perianal Cellulitis and Pneumonia in a Leukemic Child - Zeynep Canan Özdemir; Ayşe Bozkurt Turhan; Özcan Bör (Galenos Yayinevi, 2018)
Infections caused by Stenotrophomonas maltophilia may be fatal in diseases such as leukaemia which causes immunodeficiency. Herein, we report a rare case of 8-year-old girl with acute lymphoblastic leukaemia, who developed perianal cellulitis and pneumonia secondary to S. maltophilia bacteraemia while undergoing broad spectrum antimicrobial agents for neutropenic fever.